Study of Al Addition on Sintered CuCrFeNiTi as a Potential Alloy for Automotive Components - Enrique Rocha-Rangel; Ivanovich Estrada-Guel; José A. Castillo-Robles; José A. Rodríguez-García; Carlos G. Garay-Reyes; Alejandro Villalobos-Aragón; Cynthia D. Gómez-Esparza; Carlos Adrián Calles-Arriaga; Roberto Martínez-Sánchez (Metals, 2022)
CrCuFeNiTiAlx high-entropy alloys (where x = 0, 0.5, 1.0, 2.5 and 5.0 mol percent or mol %) were processed through powder metallurgy. Aluminum concentration was varied in the alloy to determine its effect on the microstructure and phase formation within the CrCuFeNiTiAlx system. X-ray diffraction (XRD) studies revealed the presence of structures mainly composed of FCC and BCC solid-solution (SS) phases in the CrCuFeNiTi alloy. The addition of aluminum content is responsible for an increased volume fraction of the BCC phase on the sintered alloys. XRD results also indicate the formation of compounds of a chemical composition and crystalline structure different from those of FCC and BCC SS phases. The presence of these compounds was also confirmed through mapping of elements and punctual chemical analysis through energy dispersive spectroscopy (EDS). Bulk samples exhibited microstructures with multimodal grain size. From the microhardness test results, it was determined that addition of Al is proportional to an increase in hardness.